Komunikasi Imajinasi dalam Film Nussa: Imagination Communication in Nussa Film - Andika Mustaqim (TOTOBUANG, 2022)
This study explores the communication of imagination in the film Nussa (2021). Using an imagination approach in discourse and action (Riceour 1993), this study reveals several aspects and the strategies of imagination of communication in children's films. In addition, the psychoanalytic approach (Freud, 1919, 1971, 1927) also become the basis in analyzingÂ  The communication of imagination because it is related to the human subconscious. The research method applied narrative analysis with a topic and visual approach. This study finds that aspects of imagination communication in the film Nussa are innovation, dreams, and complementary and inseparable ambitions . Then, the strategy of communication of imagination are the construction of identity, the encouragement of competition, the exemplarity and family support. The value and essential lesson about the communication of imagination is to be confident in yourself and optimistic about the future. Keywords: Communication, imagination, Nussa